Global distribution and status of introduced Siberian chipmunks Eutamias sibiricus. (12th February 2018) - Mori, Emiliano; Zozzoli, Rudy; Menchetti, Mattia
Abstract: Among invasive alien species, squirrels are prominent because of their popularity as pets and their positive perception by the general public. In Europe, populations of five alien squirrel species are reported. The pet trade represents a high‐risk pathway for the introduction of rodents, which are likely to become invasive because of their reproductive biology and wide native distribution ranges. In the European Union, a trade ban has been imposed on some particularly impacting species, such as the eastern grey squirrel Sciurus carolinensis . Eradication and numerical control is needed for most introduced squirrels in Europe (including the Siberian chipmunk), according to European Union Regulation 1143/2014 on alien species. We summarise the current distribution of the ground‐dwelling Siberian chipmunk Eutamias sibiricus, one of the most common pet squirrels in Europe and Asia, in its invasive range. Established populations of Siberian chipmunk, in most cases composed of small numbers of individuals, currently occur in France, Switzerland, Italy, Germany, Belgium, the Netherlands, Denmark, and Russia. The species was present in Austria, Sweden, and Hong Kong, and unsuccessful introductions occurred in Spain and the British Isles. The first records from Greece are also reported. Most introductions took place during the 1990s, when individuals were intentionally released (67% of extant populations result from such releases). Population size was correlated with the proximity to urban areas. Human risk of infection with the agent of Lyme borreliosis seems to be the highest where populations of alien Siberian chipmunk occur. Other impacts have never been reported. Competition with native rodents (e.g. the red squirrel Sciurus vulgaris and dormice, Gliridae) has been speculated on, as well as predation on nests of native warblers (Sylvidae). Impacts by alien Siberian chipmunks have been overlooked for a long time. Despite this, given that the species may affect native biodiversity and human health, eradication of established populations is recommended.